Comparison of surgically induced astigmatism following different glaucoma operations - Tanito, Masaki; Matsuzaki, Yukari; Ikeda, Yoshifumi; Fujihara, Etsuko (Clinical ophthalmology (Auckland, N.Z.), 2017)
To compare surgically induced astigmatism (SIA) among glaucomatous eyes treated with trabeculectomy (LEC), EX-PRESS shunt (EXP), ab externo trabeculotomy (exLOT), or microhook ab interno trabeculotomy (μLOT). Eighty right eyes of 80 subjects who underwent LEC (n=20), EXP (n=20), exLOT (n=20), or μLOT (n=20) were included. The dataset including the best-corrected visual acuity (BCVA), intraocular pressure (IOP), and keratometry recordings preoperatively and 3 months postoperatively was collected by chart review. The means of the vector magnitude, vector meridian, and arithmetic magnitude of the preoperative and postoperative astigmatism and SIA were calculated. The correlations among the SIA magnitude, postoperative BCVA, and IOP were assessed. The mean astigmatic arithmetic magnitudes did not differ significantly ( =0.0732) preoperatively among the four groups, but the magnitude was significantly ( =0.0002) greater in the LEC group than the other groups postoperatively. The mean SIA vectors were calculated to be 1.01 D at 56°, 0.62 D at 74°, 0.23 D at 112°, and 0.12 D at 97° for the LEC, EXP, exLOT, and μLOT groups, respectively. The mean SIA arithmetic magnitudes were significantly ( <0.0001) greater in the LEC group than the other groups. Three months postoperatively, the SIA magnitude was correlated positively with the logarithm of the minimum angle of resolution (logMAR) BCVA ( =0.3538) and negatively with the IOP ( =-0.3265); the logMAR BCVA was correlated negatively with the IOP ( =-0.3105). EXP, exLOT, and μLOT induce less corneal astigmatism than LEC in the early postoperative period.